Răspunsuri

2014-10-08T16:05:17+03:00
21x - 35 + 23 = 114
21x = 114 + 35 - 23
21x = 126
x = 126 : 21
x = 6
20x +35 - 32 = 63
20x = 63 - 35 + 32
20x = 60
x = 60 : 20
x = 3
51 - 14x - 4 = 19
- 14x = - 51 + 4 + 19
- 14x = - 28
x = 28/14
x = 2
45 - 27x + 71 = 89
- 27x = 89 - 45 - 71 
- 27x = - 27
x = 27 : 27
x = 1
(4x + 5) : 13 = 41 - 36
4x + 5 = 5 * 13
4x = 65 - 5
4x = 60
x = 60/4
x = 15
(3x + 2) : 4 = 3 + 2
3x + 2 = 5 * 4
3x = 20 - 2
3x = 18
x = 18 : 3
x = 6
(3x - 1 1) : 2 = 20 - 12
3x - 11 = 8 * 2
3x = 16 - 11
3x = 5
x = 5/3